Extraction of Poly Phenols from Cladium Mariscus Seeds and studying its Antifungal Activity with Isolation and Identification of one Compound of Flavone Glycosides - Husam M. Kredy (Journal of Global Pharma Technology, 2018)
Cladium mariscus is one of the plants belonging Cyperaceae family. It is a common plant in AL- Hammar marshes, eastern - south of Iraq. The aim of the present study was extraction poly phenols from C. mariscus seeds by using an ultrasonic-assisted extraction method. The yield of poly phenols extracted by this method was (0.43% w/w). One compound was isolated from the methanolic extract of the plant seeds. The structure of the new compound was identiﬁed via the basis of extensive spectroscopic analyses (UV-Vis, IR, 1H NMR, and Mass),  and some chemical test. Acacetin glycosides were expected compound, and the methods of spectroscopy showed that there are three molecules of hexagonal sugars linked with aglycone. The antifungi activity of methanolic extract was examined against fungus: A.flavus, A.fumigatus and C.albicans, by using the well disk diffusion method. The extract showed a clear inhibition effect against fungal at (50 %, 75 % and 100 % w/v) concentrations.  Key words: Ultrasound-assisted extraction, Cladium mariscus, Acacetin glycosides, Antifungal.